Bioequivalence studies on some selected brands of ciprofloxacin hydrochloride tablets in the Nigerian market with ciproflox® as innovator brand - Osonwa Uduma E., Agboke Ayodeji A., Amadi Rosemary C., Okorie,Ogbonna, Opurum Christian C (Journal of Applied Pharmaceutical Science)
This work assesses the bioequivalence of four selected brands of ciprofloxacin hydrochloride in the Nigerian market to Ciproflox® as a selected innovator brand. The brands selected were reperesented by samples A, B, C and D all are of Asian origin. The following parameters were employed in the assay- Weight uniformity, tablet hardness, friability, disintegration time and dissolution profile in 0.1N HCl , and minimum inhibitory concentration (MIC) determined by zones of inhibition on clinical isolates of Staphylococcus aureus. The mean hardness results were in the order Ciproflox(R) (14.55 ± 3.97) > C (12.51 ± 3.01) > D (9.87 ± 2.38) > B (9.67 ± 1.37) > A (8.98 ± 3.46) and they all fell within the acceptable values of 3 kgs =.hardness. The mean friability results were in the order A (0.07)
Keywords: Ciprofloxacin hydrochloride,tablets,brands,bioequivalence,tablet characteristics,microbiological.